MITIGATING METHANE EMISSIONS FROM ERBIL WASTE DUMPING SITE: A GIS –BASED APPROACH TO DETECTION AND CONVERSION INTO A GREEN LANDSCAPE - AZIZ, SHUOKR QARANI; KAREEM, DALSHAD AHMED; SLEEM, BALA KAWA M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This work uses Geographic Information System (GIS) technology, particularly ArcMap, to address the serious environmental issue of methane (CH4) leaks from the Kane Qrzhala waste dumping site Sub district in Erbil City, at latitudes 36°10’23"- 36°52’25" N and longitudes 43°35’32"- 44°23’43" E. The aim of this research is to identify and analyze methane concentrations in the neighborhood of the dumping site, offering significant data for environmental monitoring and mitigation techniques. "This study employs an integrated approach combining spatial data and satellite imagery. Methane emission levels were extracted from two publicly accessible platforms: earth.jpl.nasa.gov and dataspace.copernicus.eu.”, and ground measurements to map and quantify methane emissions. The findings contribute to the understanding of the spatial distribution of methane emissions, enabling targeted interventions to reduce environmental harm. Furthermore, the research investigates sustainable alternatives to reducing methane emissions by identifying that the garbage dumping site be converted into a green area and, eventually, a forest. The methane plume spanned 26.768 km² with a concentration of 3471 ppm—over twice the safety limit—posing a serious environmental and health risk and demanding urgent action to control emissions. Beyond methane reduction, the benefits of transforming the dumping site into a green space include improved air quality, increased biodiversity, and the construction of a community recreational area. Finally, this study not only extends to our awareness of the release of methane from waste disposal sites, however it also advocates for the conversion of such sites into environmentally beneficial landscapes.